Surface modification of poly(vinylidene fluoride) hollow fibre membranes for biogas purification in a gas–liquid membrane contactor system. Issue 11 (15th November 2017) - Jin, Pengrui; Huang, Chuan; Li, Jiaxiang; Shen, Yadong; Wang, Liao
Abstract : The wetting of hollow fibre membranes decreases the performance of the liquid–gas membrane contactor for CO2 capture in biogas upgrading. To solve this problem, in this work, a poly(vinylidene fluoride) (PVDF) hollow fibre membrane for a liquid–gas membrane contactor was coated with a superhydrophobic layer composed of a combination of hydrophobic SiO2 nanoparticles and polydimethylsiloxane (PDMS) by the method of spray deposition. A rough layer of SiO2 deposited on the PVDF membrane resulted in an enhanced surface hydrophobicity. The surface structure of the pristine PVDF significantly affected the homogeneity of the generated SiO2 layer. A uniform surface coating on the PVDF upper layer resulted from the presence of micrometre and nanometre-sized roughness on the surface of the PVDF membrane, which was achieved with a SiO2 concentration of 4.44 mg ml −1 (0.2 g/45 ml) in the coating solution. As a result, the water contact angle of the modified surface was recorded as 155 ± 3°, which is higher than that of the pristine surface. The high contact angle is advantageous for reducing the wetting of the membrane. Additional mass transfer resistance was introduced by the superhydrophobic layer. In addition, continuous CO2 absorption tests were carried out in original and modified PVDF hollow fibre membrane contactors, using monoethanolamine (MEA) solution as the absorbent. A long-term stability test revealed that the modified PVDF hollow fibre membrane contactor was able to outperform the original membrane contactor and demonstrated outstanding long-term stability, suggesting that spray deposition is a promising approach to obtain superhydrophobic PVDF membranes for liquid–gas membrane absorption.